Ending Toxicity: A Call to Reintroduce Constructive Discourse About Contentious Health-Related Issues in Medicine - Downie, Jocelyn (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
There is a disturbing phenomenon of physicians viciously attacking other physicians when they disagree with them on contentious health-related issues. Such attacks have significant potential negative impacts on patient care, physician well-being, and public policy. Reflection on and responses to this phenomenon are needed.